Humoral Immune Response to the Anti-malaria Vaccine SPf66 in the Colombian Atrato River Region (1998)
ABSTRACT: The immunogenicity of anti-malaria synthetic vaccine SPf66 was tested in a region of the Colombian middle Atrato river. The specific serum antibodies against SPf66 were quantified in vaccinees and placebo injected controls for a two-years period post-immunization. The frequency of individuals showing seroconversion of anti-SPf66 antibodies three months after completion of the immunization schedule was higher in vaccinees than in controls (52.7% and 25.5%, respectively, p<0.01). However, an over than four-fold increase of the specific anti-SPf66 antibody titers was observed only in 1.4% of vaccinees and 0.2% of the controls (p<0.01). The anti-SPf66 antibody titers augmented in vaccinees from first dose application to three months after the third dose, continuously decreasing thereafter to reach below baseline values two years after completion of the immunization schedule. The results show that SPf66 has very low immunogenicity and induces a short term humoral immune response (six months).